Highly defective porous CoP nanowire as electrocatalyst for full water splitting. (7th December 2017) - Zhang, Mengtian; Ci, Suqin; Li, Hao; Cai, Pingwei; Xu, Huimin; Wen, Zhenhai
Abstract: It is highly desirable to develop low-cost and highly-efficiency electrocatalysts toward hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) for implementing full water splitting in developing a sustainable green energy system. Herein, we report a reliable and facile anion-exchange reaction strategy for conversion of one-dimensional (1D) Co3 O4 nanowires (NWs) into CoP porous nanowires (PNWs). Notably, such evolution process provides the as-formed CoP PNWs with significantly improved defect sites and thus endows the CoP PNWs with a high electrochemical activity surface area. Accordingly, the CoP PNWs exhibit outstanding catalytic activity toward HER and OER when serving as bifunctional electrocatalysts, achieving a current density of 10 mA cm −2 with low overpotentials of 147 and 326 mV for HER and OER, respectively. We demonstrate the water splitting electrolyzer with such CoP PNWs electrocatalyst as cathode and anode can be driven by a double A battery and a solar panel (1.5 V). The advantages, including facile and low-cost synthetic process, high activity for HER and OER, endow the as-developed CoP PNWs to be one of the most promising candidates for full water splitting system. Highlights: Synthesis of highly defective porous CoP nanowire by anion-exchange strategy. High activity as bifunctional electrocatalyst for OER and HER. Water electrolysis can be driven by a solar panel with 1.5 V.